PERAN INFLUENCER DALAM PEMASARAN MEDIA SOSIAL BAGI UMKM - Ramadhani, Luna Novia; Koswara, Audri; Lutpiah, Dwi; Alhidayatullah, Alhidayatullah (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2024)
This study aims to outline influencers' function in MSMEs' social media marketing. A descriptive study using a qualitative methodology is the methodology employed. MSMEs in Sukabumi City are the study's informants. There are up to fifteen business actors at Sukabumi City's Muhammadiyah University. methods for gathering data that include literature research, interviews, and observation. Strategies for data analysis that make use of triangulation are data reduction, data display, and conclusion drafting. The results of this study can be seen from the research questions, namely the number of followers on social media, the type of social media owned, creative content, the impact of content on sales, and the number of consumers. owned, creative content, the impact of content on sales, and the number of consumers who buy on social media. Who buys on social media, explaining that marketing on social media carried out by MSMEs today must have creative and effective content. Done by MSMEs today must have creative content.